Miombo woodlands and rural livelihoods in Malawi - Lowore, J.D. (Center for International Forestry Research, 2006)
Farmers in Malawi remove woodlands to plant crops but they also derive a vast range of other basic needs from the surrounding forests. These miombo woodlands have until relatively recently always been vast in comparison to the human population and their needs. Over the years the woodlands and the way they have been used have changed, but their contribution for maintaining well being and providing peoples’ basic needs appears to have remained important. The main changes in the woodlands are a decrease in the area of woody plants remaining and the nature of the interface between woodlands and people. Forest area has reduced considerably; about 2.5 million hectares of forest land were converted to agricultural land between 1946 and 1996 (Openshaw, 1997). The nature of the interface between people and miombo – once limited to being a superstore of products for the home, the farm and the hunt – has increased in complexity. The purpose of this booklet is to explore some of the dimensions of the people/miombo interface and in particular identify those key areas that are most crucial for food security and poverty alleviation.